Occurrence of greigite in the Pliocene sediments of Lake Qinghai, China, and its paleoenvironmental and paleomagnetic implications. (8th May 2015) - Fu, Chaofeng; Bloemendal, Jan; Qiang, Xiaoke; Hill, Mimi J.; An, Zhisheng
Abstract Lake Qinghai in North China is the largest interior plateau lake in Central Asia and is climatically sensitive. An almost continuous 626 m long sediment core was drilled in an infilled part of the southern lake basin of Lake Qinghai. The magnetic susceptibility record reveals the presence of two distinct peaks within an interval of fine‐grained lacustrine sediments of Lower Pliocene age. We selected a depth interval of approximately 40 m spanning the magnetic susceptibility peaks for detailed rock magnetic and geochemical analyses in order to identify the magnetic mineralogy responsible and to assess its possible paleoenvironmental and paleomagnetic implications. Rock magnetic, X‐ray diffraction analysis, scanning electron microscopy (SEM), and energy dispersive analysis of X‐ray (EDAX) analyses reveal that the main magnetic carrier is greigite (Fe3S4). The greigite is of early diagenetic origin and formed in an inerval of high lake level and inferred relatively warm, humid climate. The greigite‐enriched zones are separated by an interval of relatively high total sulfur and organic carbon content, and we infer that in the adjacent greigite‐bearing zones, the lower concentrations of sulfur and organic carbon, and high levels of reactive iron, arrested the process of pyritization resulting in the preservation of the greigite on a time scale of several million years. The greigite zones contain narrow intervals of normally magnetized sediments which may be previously unrecognized cryptochrons within the Gilbert Chron, or alternatively they may reflect the continued formation of greigite long after the age of deposition of the surrounding sediment matrix.